PEFA Assessment of Gender Responsive Public Financial Management : Ukraine - World Bank (World Bank, Kyiv, 2021)
This assessment of gender responsive public financial management (GRPFM) for 2020 of the government of Ukraine (GoU) has been conducted using the draft Supplementary Framework for Assessing Gender Responsive Public Financial Management and is one of the first pilots using this framework. The purpose of the PEFA supplementary assessment on gender responsive budgeting (GRB) is to collect information on the extent to which gender is mainstreamed in Ukraine’s public financial management (PFM) system and to establish a baseline for future assessments. The government of Ukraine has been at the forefront of introducing and mainstreaming gender, so the assessment results are expected to facilitate the measurement of progress on an initiative that is already underway.